Arms production, national defense spending and arms trade: Examining supply and demand - Johannes Blum (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Scholars have estimated demand functions for national defense spending and investigated international arms trade for a long time. The relationship between supply and demand for military goods has, however, only been examined on aggregate level or in formal models yet. I investigate how the supply of military goods by arms-producing companies and the demand for military goods by both the national government and foreign governments are related by using a panel of up to 195 arms-producing companies in 21 countries for the period 2002-2016. The results show that if the demand for national defense spending increases by 1%, the arms sales by a country's largest arms-producing companies increase by up to 1.2%. If exports of major conventional weapons increase by 1%, sales increase by up to 0.2%. Arms imports do not affect domestic arms sales because imported and domestically produced arms are complements, and countries mainly import those arms they do not produce themselves. Country-specific estimation results suggest that differences among countries in geopolitical conditions and international relations determine whether a country's arms industry serves economic rather than security purposes.
Keywords: L64; F14; H56; C23; 330; arms industry; arms trade; defense spending; panel data